2015
DOI: 10.1186/s12889-015-2438-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different radon guideline values based on characterization of ecological risk and visualization of lung cancer mortality trends in British Columbia, Canada

Abstract: BackgroundThere is no safe concentration of radon gas, but guideline values provide threshold concentrations that are used to map areas at higher risk. These values vary between different regions, countries, and organizations, which can lead to differential classification of risk. For example the World Health Organization suggests a 100 Bq m−3value, while Health Canada recommends 200 Bq m−3. Our objective was to describe how different thresholds characterized ecological radon risk and their visual association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The improvements in data collection and availability will be valuable for future campaigns and for determining where collaborative efforts are most needed [ 35 ]. Measuring and mitigating radon at schools should be based on ALARA (As Low As Reasonably Achievable), the precautionary principle to minimize radiation doses and releases of radioactive materials with using practical, cost-effective measures [ 4 , 36 , 37 ]. Therefore, we recommend that a federally mandated maximum radon limit be established for schools and other buildings with public access, as should guidelines regarding the timeframe for initial testing and the frequency of re-testing for radon.…”
Section: Discussionmentioning
confidence: 99%
“…The improvements in data collection and availability will be valuable for future campaigns and for determining where collaborative efforts are most needed [ 35 ]. Measuring and mitigating radon at schools should be based on ALARA (As Low As Reasonably Achievable), the precautionary principle to minimize radiation doses and releases of radioactive materials with using practical, cost-effective measures [ 4 , 36 , 37 ]. Therefore, we recommend that a federally mandated maximum radon limit be established for schools and other buildings with public access, as should guidelines regarding the timeframe for initial testing and the frequency of re-testing for radon.…”
Section: Discussionmentioning
confidence: 99%
“…Men being more aware of the risks of radon exposure, will test houses more often but are less concerned and less affected compared to women (Poortinga, 2008(Poortinga, , 2011. Temporal trends in lung cancer mortality are increasing for women while decreasing for men (Branion-Calles et al, 2015). However, it is not yet clear whether this is due to the increasing rates of smoking among women or due to their spending more time indoors.…”
Section: Review Outcomesmentioning
confidence: 93%
“…12 Several studies, including exposure assessment, risk assessment, and epidemiological studies, have reported that radon exposure has a signicantly positive association with an increased incidence and mortality of lung cancer. [13][14][15][16][17] However, some recent studies showed that the risk of lung cancer could be signicantly elevated by not only radon but also other nonoccupational factors. Two studies reported the possibility of a joint effect of smoking and radon exposure, [18][19][20] and another study also demonstrated that the risk of lung cancer mortality was signicantly associated with nonoccupational factors, including nationality, region, education, and smoking history, rather than radon exposure.…”
Section: Introductionmentioning
confidence: 99%